PENGARUH PERSEPSI CINTA MEREK TERHADAP CITRA MEREK, KETERLIBATAN MEREK, DAN SIKAP TERHADAP MEREK PADA PRODUK IPHONE DI KOTA BANDA ACEH - Muhammad Rezky Fitrah, Iskandarsyah Madjid (Departemen Manajemen, 2018)
This study aims to determine the effect of Brand Love Perception Against Brand Image, Brand Engagement, and Brand Attitudes on iPhone Products in Banda Aceh. The samples used in this study are iPhone brand Users located in Banda Aceh who have the iPhone brand experience or not. This research method used questionnaire as research instrument. From 120 questionnaires distributed using google form, and finally the researchers got 134 questionnaires that can be analyzed. Purposive Sampling is used as a sampling technique. This technique places specific criteria in sampling. Multiple regression analysis method is used as a method of analysis to determine the effect of the variables involved. The results of this study indicate that the influence of Brand Love perception Against Brand Image, Brand Engagement, and Brand Attitudes on iPhone Products in Banda Aceh. have a significant effect on the Brand Love of iPhone Products. Keywords: Brand Love, Brand Image, Brand Engagement, Brand Attitudes.